ANSWER:
1st option: f(x) = -f(-x)
Explanation:
The polynomial function is symmetric about the origin in the odds functions, where the following is true:
![\begin{gathered} f(-x)=-f(x) \\ \\ \text{ Therefore:} \\ \\ f(x)=-f(-x) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6rtxzxmbl1rp73ws7c46e0thua89kvysya.png)
Then it would be:
If f(x) = -f(-x), then the graph of the polynomial function is symmetric about the origin.
The correct answer is the 1st option: f(x) = -f(-x)